No Single Feeding Method was Universally Superior Across All Clinical Outcomes during the Transition from Gavage to Oral Feeding in Preterm Infants - Rian Primadi Sukoco; Allenidekania Allenidekania; Yeni Rustina; Robiyatul Adawiyah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Feeding difficulties are a major cause of prolonged hospitalization and delayed discharge among preterm infants in neonatal intensive care units. Although multiple feeding methods have been introduced to support the transition from gavage feeding to oral feeding, evidence regarding their comparative effectiveness remains inconsistent. This systematic review aimed to compare the effectiveness of different feeding methods used during the transition from gavage feeding to oral feeding in preterm infants, and to determine how each method influences physiological stability, feeding performance, and breastfeeding outcomes. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta‑Analyses guidelines. Searches were conducted in PubMed, ScienceDirect, ProQuest, Scopus, and EBSCOhost for study publications between 2010 and 2025. Randomized controlled trials and quasi‑experimental study designs were included, and methodological quality was assessed using Joanna Briggs Institute appraisal tools. Nine studies involving 1,065 preterm infants were included. Paced bottle feeding with elevated side‑lying positioning improved coordination of sucking, swallowing, and breathing. Cup feeding supported higher exclusive breastfeeding rates after discharge. Syringe feeding accelerated the transition to full breastfeeding and promoted greater physiological stability. Finger feeding reduced feeding‑related complications but required longer feeding time. Novel teat systems and supplemental feeding tube devices showed encouraging results, although evidence remained limited. No single feeding method demonstrated consistent superiority across all outcomes. Feeding strategies should be individualized according to infants’ physiological readiness, clinical stability, breastfeeding goals, and available neonatal intensive care unit resources.Keywords: preterm infants; oral feeding; cup feeding; syringe feeding; finger feeding; paced bottle feeding